Incorporación del eje laboral obligatorio para las personas con sentencia condenatoria ejecutoriada; para evitar un déficit económico para el estado - Sánchez Espinoza, Lady Geovanna (2022)
The present research work is entitled: "Incorporation of the Mandatory Labor Axis for People with An Enforceable Conviction to avoid an Economic Deficit for the State", and the importance of studying this issue is due to the fact that the crisis in the Penitentiary System has been increasing in recent years becoming a latent problem that threatens the security not only of people deprived of liberty, but also of the State and society in general. The research that has been carried out shows that the lack of incorporating persons deprived of liberty into productive activities in this case the work that would allow physical and mental development, makes it possible for them not to organize or properly use their free time, thus giving rise to them incurring in the commission of acts that threaten their safety and that of third parties. In this thesis, materials and methods were applied that allowed the development of the research, as well as interviews and surveys were conducted with legal professionals, results that served to propose the draft legal reform of the Organic Integral Penal Code and National Regulations of Social Rehabilitation, with the purpose of establishing work for prisoners as mandatory and thus guaranteeing the rights of persons deprived of liberty and at the same time contributing to the State by reducing the budget allocated for this task.